2019
DOI: 10.1016/j.bbapap.2018.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Imaging individual protein aggregates to follow aggregation and determine the role of aggregates in neurodegenerative disease

Abstract: Protein aggregates play a key role in the initiation and spreading of neurodegenerative disease but have been difficult to study due to their low abundance and heterogeneity, in both size and structure. Fluorescence based methods capable of detecting and characterising single aggregates have recently been developed and can be used to measure many important aggregate properties, and can be combined with sensitive assays to measure aggregate toxicity. Here we review these methods and discuss recent examples of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Single particle techniques are unparalleled in their ability to directly detect individual molecules and populations of interconverting species within heterogeneous mixtures. Single particle fluorescence methods (a term we use here to describe approaches which rely on fluorescent dyes, rather than the measurement of intrinsic protein fluorescence) and SPFS have both played key roles in the amyloid field, allowing kinetic and low-resolution structural information to be obtained for the species populated during fibril assembly [ [67] , [68] , [69] ]. Other non-ensemble averaged methods, such as ESI-MS, are also able to directly detect specific oligomer populations during assembly.…”
Section: Non-perturbing Methods For the Study Of Amyloid Oligomersmentioning
confidence: 99%
“…Single particle techniques are unparalleled in their ability to directly detect individual molecules and populations of interconverting species within heterogeneous mixtures. Single particle fluorescence methods (a term we use here to describe approaches which rely on fluorescent dyes, rather than the measurement of intrinsic protein fluorescence) and SPFS have both played key roles in the amyloid field, allowing kinetic and low-resolution structural information to be obtained for the species populated during fibril assembly [ [67] , [68] , [69] ]. Other non-ensemble averaged methods, such as ESI-MS, are also able to directly detect specific oligomer populations during assembly.…”
Section: Non-perturbing Methods For the Study Of Amyloid Oligomersmentioning
confidence: 99%
“…The transient nature of oligomers makes them difficult to isolate and characterize at the structural level. Only recently, thanks to new approaches such as single molecule fluorescence and electron microscopy [ 14 , 17 , 18 ], has it been shown that oligomers are highly heterogeneous in their physiochemical properties and structures, with a varying secondary structure content [ 16 , 19 , 20 ].…”
Section: Amyloid Aggregation As Potential Source Of Biomarkersmentioning
confidence: 99%
“…Notably, fluorescence-based methods provide ultrasensitive detection of individual amyloid fibrils and oligomers in neurodegenerative diseases. Furthermore, super-resolution methods offer insight into structural properties and surface hydrophobicity [ 17 ].…”
Section: Recent Advances In Detection Technologymentioning
confidence: 99%
“…This is consistent with the amyloid-like properties reported in LBs; however interestingly SOD1 aggregates appear to exhibit non-amyloid properties. 8 Nonetheless, SOD1 and LB aggregates both demonstrated inconsistent morphology, and both exhibited a wide range of sizes, ($5-60 mm 2 ), suggesting that they may be in varied maturation states of aggregate formation.…”
Section: Lb and Sod1 Demonstrate Ordered Structuresmentioning
confidence: 99%
“…Impaired or aberrant binding of the essential biometals Cu, Fe and Zn, in particular has been implicated in increasing the propensity of proteins to misfold and deposit within the central nervous system. Subcellular imaging of human post-mortem tissues provides insights into the biochemical mechanisms that underlie the formation of these pathological features in disease processes 2 and is more widely applicable to other disease states and tissues.…”
Section: Introductionmentioning
confidence: 99%